On the structure of some non-periodic groups whose subgroups of infinite special rank are transitively normal - Velychko, T.V. (Carpathian Mathematical Publications, 2021)
A group G has a finite special rank r if every finitely generated subgroup of G is generated by at most r elements and there is a finitely generated subgroup of G which has exactly r generators. If there is not such r, then we say that G has infinite special rank. In this paper, we study generalized radical non-abelian groups of infinite special rank whose subgroups of infinite special rank are transitively normal.